CD34 and CD38 are prognostic biomarkers for acute B lymphoblastic leukemia. Issue 1 (December 2016) - Jiang, Zhiwu; Wu, Di; Lin, Shouheng; Li, Peng
Abstract CD34 and CD38 proteins are usually used as surface markers to identify HSCs and Leukemic stem cells. However, there have been cases that lacked CD34 or CD38 protein but still had leukemia initiating capacity in B-ALL suggesting the restrictive of these two markers. CD34 and CD38 expression were detected in most B-ALL and can serve as a specific biomarker for the prognosis of this subset of leukemia. Lack of CD34 or high CD38 expression is associated with favorable prognosis.